Nuclear receptor NR2F6 inhibition potentiates responses to PD-L1/PD-1 cancer immune checkpoint blockade - Victoria Klepsch (Nature Portfolio, 2018)
Immune checkpoints blockade (ICB) is a viable anti-cancer strategy. Here the authors show that nuclear receptor NR2F6 acts as an immune checkpoint in T cells and, using mouse models and human T cells, they show NR2F6 inhibition might improve current ICB therapy or work as an alternative therapeutic strategy.